Cardiac troponin T and fast skeletal muscle denervation in ageing. Issue 5 (16th April 2017) - Xu, Zherong; Feng, Xin; Dong, Juan; Wang, Zhong‐Min; Lee, Jingyun; Furdui, Cristina; Files, Daniel Clark; Beavers, Kristen M.; Kritchevsky, Stephen; Milligan, Carolanne; Jin, Jian‐Ping; Delbono, Osvaldo; et al.
Abstract: Background: Ageing skeletal muscle undergoes chronic denervation, and the neuromuscular junction (NMJ), the key structure that connects motor neuron nerves with muscle cells, shows increased defects with ageing. Previous studies in various species have shown that with ageing, type II fast‐twitch skeletal muscle fibres show more atrophy and NMJ deterioration than type I slow‐twitch fibres. However, how this process is regulated is largely unknown. A better understanding of the mechanisms regulating skeletal muscle fibre‐type specific denervation at the NMJ could be critical to identifying novel treatments for sarcopenia. Cardiac troponin T (cTnT), the heart muscle‐specific isoform of TnT, is a key component of the mechanisms of muscle contraction. It is expressed in skeletal muscle during early development, after acute sciatic nerve denervation, in various neuromuscular diseases and possibly in ageing muscle. Yet the subcellular localization and function of cTnT in skeletal muscle is largely unknown. Methods: Studies were carried out on isolated skeletal muscles from mice, vervet monkeys, and humans. Immunoblotting, immunoprecipitation, and mass spectrometry were used to analyse protein expression, real‐time reverse transcription polymerase chain reaction was used to measure gene expression, immunofluorescence staining was performed for subcellular distribution assay of proteins, and electromyographic recording was used to analyse neurotransmission at the NMJ. Results: Levels of cTnT expression in skeletal muscle increased with ageing in mice. In addition, cTnT was highly enriched at the NMJ region—but mainly in the fast‐twitch, not the slow‐twitch, muscle of old mice. We further found that the protein kinase A (PKA) RIα subunit was largely removed from, while PKA RIIα and RIIβ are enriched at, the NMJ—again, preferentially in fast‐twitch but not slow‐twitch muscle in old mice. Knocking down cTnT in fast skeletal muscle of old mice: (i) increased PKA RIα and reduced PKA RIIα at the NMJ; (ii) decreased the levels of gene expression of muscle denervation markers; and (iii) enhanced neurotransmission efficiency at NMJ. Conclusions: Cardiac troponin T at the NMJ region contributes to NMJ functional decline with ageing mainly in the fast‐twitch skeletal muscle through interfering with PKA signalling. This knowledge could inform useful targets for prevention and therapy of age‐related decline in muscle function.